Water resource management in the Olifants Basin of South Africa: previous projects and future prospects - Altchenko, Yvan; Shu, Yunqiao (2011)
The Olifants River Basin is located in the north-eastern part of the South Africa and southern to Mozambique.The Olifants River passes through three provinces of South Africa (Gauteng, Mpumalanga, Limpopo Province), through the Kruger National Park, into Mozambique, where it joins the Limpopo . it is the home to nearly 10 % of the total population of South Africa. The climate is semi-arid, with rain falling primarily during the summer (November to March). Precipitation averages 630 mm and potential evaporation is 1700mm. In South Africa, significant mining, industrial and agricultural activities (including intensive irrigation schemes) are concentrated within the catchment, so it is of considerable importance for the country's economy. However, Water is especially scarce in this basin. Like many river basins in South Africa, water resources in the Olifants river basin are almost fully allocated. Water demand management, especially in the agricultural sector, which is the biggest user, is one of the possible solutions being considered by the South African Department of Water Affairs and Forestry (DWAF). The basin also faces significant water quality problems, due to mining activities, industries, power generation and agricultural use of water. The impact of these pollutions (high salinity, high concentrations of metals, low pH) are probably multiple with serious ecological impacts. Particularly of concern in the downstream Kruger National Park which is a major tourist attraction in South Africa and more importantly very worrisome health impacts, since some people are drinking surface water without any treatment. In South Africa it is of prime importance to maintain a minimum level of water quality and quantity in the rivers in order to maintain a healthy biophysical environment (DWAF, 1997). This requirement, referred to as the 'Ecological Reserve', is as important in the South African legislation as meeting the basic human needs and must be met before any other users can abstract water. Main activities on the Olifants basin have been done through the Challenge Program on Water and Food and the WETwin project but not only.